Secondary surgery and mortality following primary treatment for acetabular fractures – an observational study from Swedish national quality registers - Madelene Albrektsson; Michael Möller; Mikael Sundfeldt; David Wennergren; Olof Wolf (Journal of Orthopaedic Surgery and Research)
Abstract Background The treatment of acetabular fractures ranges from non-operative with no restrictions in mobilisation to some of the more complex operative treatments in orthopaedics. Treatment strategies are developing, and outcomes need to be studied continuously. The study’s primary aim was to assess the rate of secondary treatment in patients with acetabular fractures treated non-operatively or operatively. A secondary aim was to study mortality. Methods Data were retrieved from the Swedish Fracture Register and cross-referenced with the Swedish Arthroplasty Register for all patients aged ≥ 18 years with an acetabular fracture between 2014 and 2023. Patients were divided into three primary treatment groups: non-operative treatment, open reduction and internal fixation (ORIF), and total hip arthroplasty (THA) with/without combined ORIF (THA/combined hip procedure, CHP). The study examined mortality rates within each treatment group. Results Of the 3318 patients included in the study, 74% were treated non-operatively, 18% with ORIF, and 8% with THA/CHP. 4% of non-operatively treated patients and 17% of patients treated with ORIF had been converted to THA at 5 years, 12% of patients with THA as primary treatment had been revised. Patients who underwent THA as their initial treatment were more likely to undergo secondary treatment early. However, in those initially treated with ORIF the prevalence of secondary treatment increased after the first year. The non-operatively treated group had the highest mortality rate (19% at 1 year), followed by the THA group (14% at 1 year). Conclusions This observational nationwide register study on acetabular fractures shows that surgically treated patients have a relatively high reoperation rate. Younger patients are predominately treated with ORIF and display low mortality rates. Older patients with complex fracture patterns may benefit from primary treatment with THA/CHP being more frequently performed compared to prevailing practice.